2021
DOI: 10.1001/jamanetworkopen.2021.26334
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Cancer Stage at Diagnosis Before and During the COVID-19 Pandemic in Japan

Abstract: Key Points Question Is the COVID-19 pandemic associated with the stage at which gastrointestinal cancer is diagnosed in Japan? Findings In this cohort study of 5167 patients, significant decreases were observed for the diagnosis of stage I gastric cancer and stage 0 to II colorectal cancer, whereas a significant increase was observed for the diagnosis of stage III colorectal cancer. Meaning These findings suggest that during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 35 publications
9
78
0
4
Order By: Relevance
“…In the past months, a substantial body of literature has investigated the effects of the COVID-19 crisis on cancer diagnosis (Andrew et al 2021 ; De Luca et al 2021 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2020 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). For example, a study, using national data from New Zealand, showed that cancer registrations (new diagnoses of primary malignant cancers) declined by 40% in this country in March–April 2020 compared with 2018–2019, and that registrations increased in the subsequent months to reach pre-lockdown levels (Gurney et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past months, a substantial body of literature has investigated the effects of the COVID-19 crisis on cancer diagnosis (Andrew et al 2021 ; De Luca et al 2021 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2020 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). For example, a study, using national data from New Zealand, showed that cancer registrations (new diagnoses of primary malignant cancers) declined by 40% in this country in March–April 2020 compared with 2018–2019, and that registrations increased in the subsequent months to reach pre-lockdown levels (Gurney et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of the COVID-19 pandemic on the care of acute and chronic disorders may be explained, at least partially, by overwhelmed healthcare systems (Tangcharoensathien et al 2021 ) and the fear of patients to consult primary care practices and emergency departments due to the potential risk of being infected by the SARS-CoV-2 (Czeisler et al 2020 ; Lazzerini et al 2020 ). Some literature also suggests that COVID-19 has been associated with a substantial decrease in cancer diagnosis (Andrew et al 2021 ; De Luca et al 2021 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2020 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). Interestingly, a study conducted in Germany found that cancer diagnoses decreased in March–May 2020 compared with March–May 2019, and this decrease was particularly strong for cancers of the skin and the respiratory and intrathoracic organs (Jacob et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no indication of widespread serious medical disruption in Japan by April 2021, patients might have refrained from visiting hospitals to receive medical checkups, including gastric cancer screening, because of the COVID-19 pandemic. In Japan, a significant decrease in the mean number of stage I gastric cancer cases and an increase in the number of symptomatic gastric cancer patients were observed during the COVID-19 pandemic from March to December 2020 [ 6 ]. In another Japanese study, the number of gastrectomies was < 80%, and there was a 50% decrease from May to August 2020 in Tokyo when compared to the previous year as determined using questionnaires [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single-centre study in the UK reported a reduction in the number of patients referred for oesophageal cancer during the pandemic compared with the same period in 2019 ( 4 ). In Japan, a recent study on the status of oesophageal cancer consultations revealed no significant differences; however, the number of patients with stage 0 to II disease decreased, whereas that of patients with stage III or IV disease increased ( 5 ).…”
Section: Introductionmentioning
confidence: 93%